Escolítidos asociados en árboles de Tectona grandis L.f. enfermos con marchitez váscular y muerte regresiva en la Provincia de Esmeraldas, año 2018. - Valencia Merchán, Sandy Lissette. (2018)
The present research project was developed in three sites located in the parish of San Mateo, province of Esmeraldas. The objectives of this research were; identify and determine the scolityd associated with teak trees with vascular wilt symptomatology and regressive death, present in plantations located in the parish of San Mateo, province of Esmeraldas. Plots of 500 m2 were established. The collection of samples was made in four days of July 2018. The collection was collected and a five-category scale was used to establish the severity of the disease depending on the physiological characteristics of the leaves, branches and shaft. In terms of diversity, abundance and richness, these parameters were calculated using the indices of Margaleff, Shannon and Simpson. The identification was carried out with the help of dichotomous Keys were developed by Wood (17), by observing the morphological characteristics of the insects, with the help of a stereoscope that facilitated in the work. A total of 771 scolitid was registered, with the site 1 "Zambrano" where the largest number of individuals with 559 (72.50%) were registered, represented by the tribe Xylebirini, Ipini and Cryphalini within these were represented the species Xyleborus ferrugineus, Xyleborus affinis and Coptoborus sp, belonging to the Xyleborini tribe, while in the Ipini tribe there was only presence of the Premnobius Cavipenis sp and the tribe Crypalini showed presence of Hypothenemus sp. In Site 2 "La Mala", 149 (19.33%) individuals were obtained, which were Xyleborus ferrugineus Coptoborus sp. belonging to the Xyleborini tribe and the Premnobius Cavipenis sp. belonging to the Ipini tribe. Finally, on site 3 "Tepeyac" registered 63 (8.11%) individuals having only the presence of the tribe Xyleborini the species Xyleborus ferrugineus. These species are considered as pests, as they affect the plantation causing damage, and thus cause great economic losses.